Metaverse in journal publishing - Kim, Kihong (Science Editing, 2022)
Recently, the word metaverse has appeared more and more frequently in media reports and public discourses. Most of them are predictions of the future in the science fiction style that a new kind of world will come when the metaverse technology is successfully implemented and they do not give a sense of reality yet. Lectures on metaverse are frequently held in many academic disciplines. At the annual general meeting of the Korean Council of Science Editors held last month, an introductory talk on metaverse was given as a plenary lecture. According to the Amazon site, there are 821 books published after January 2020 with “metaverse” in their titles. According to the Kyobo Books website, there are 238 Korean books that contain the word metaverse in Korean in their titles. That such a tremendous amount of interest is being given to a technology that has not yet been realized is a very unusual and unprecedented phenomenon. The rapid development of information technology over the past few decades is thought to convince people that the metaverse can be implemented in a short period.